2012
DOI: 10.1371/journal.pone.0050643
|View full text |Cite
|
Sign up to set email alerts
|

Annual Glyphosate Treatments Alter Growth of Unaffected Bentgrass (Agrostis) Weeds and Plant Community Composition

Abstract: Herbicide resistance is becoming more common in weed ecotypes and crop species including turfgrasses, but current gaps in knowledge limit predictive ecological risk assessments and risk management plans. This project examined the effect of annual glyphosate applications on the vegetative growth and reproductive potential of two weedy bentgrasses, creeping bentgrass (CB) and redtop (RT), where the glyphosate resistance (GR) trait was mimicked by covering the bentgrass plants during glyphosate application. Five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Our data on plant species diversity and community composition of a fallow field support these findings. However, some studies have suggested that herbicides may not reduce the diversity of plant communities in agricultural landscapes 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Our data on plant species diversity and community composition of a fallow field support these findings. However, some studies have suggested that herbicides may not reduce the diversity of plant communities in agricultural landscapes 42,43 .…”
Section: Discussionmentioning
confidence: 99%